Eco-Friendly Media: Assistance in Developing Educational Props from Waste Materials in Probolinggo City - Umar Manshur; Fathor Rozi; Latifatus Saleha; Chodijatus Sholihah (GUYUB: Journal of Community Engagement, 2024)
This community engagement was driven by the limitations of resources and adequate facilities within the early childhood education environment. The restricted or monotonous use of educational props, coupled with financial limitations within the institution, constrains the variety and creativity in the learning process. Additionally, the lack of understanding regarding the potential use of waste materials as educational props hinders more engaging teaching innovations. This community engagement aimed to introduce the creation of educational props using waste materials available within the school environment by providing engaging learning stimuli, thereby making the content delivered by teachers more effective and efficient. The approach used in this community engagement was Asset-based Community Development (ABCD). The approach enables the community to build upon existing strengths without depending on external assistance. This approach began by identifying the assets possessed by the community, which were then utilized to develop the educational institution. The outcomes of this engagement indicated some important points. First, teachers, in early childhood educational institutions in Probolinggo City, understood appropriate stimuli for the growth and development of students, demonstrating competence in pedagogic skills as one of the essential competencies for teachers. Secondly, teachers in these institutions could utilize waste materials to create Educational Play Tools (EPT) through identifying recyclable waste, training, and practical application in crafting these tools. Thirdly, teachers were capable of harnessing local potential previously untapped, which could be used to support learning activities by turning them into Educational Play Tools (EPT).